2011
DOI: 10.1186/1752-1947-5-404
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral testicular self-castration due to cannabis abuse: a case report

Abstract: IntroductionThe self-mutilating patient is an unusual psychiatric presentation in the emergency room. Nonetheless, serious underlying psychiatric pathology and drug abuse are important background risk factors. A careful stepwise approach in the emergency room is essential, although the prognosis, follow-up, and eventual rehabilitation can be problematic.We present a unique and original case of bilateral self-castration caused by cannabis abuse.Case PresentationWe report a case of a 40-year-old Berber man, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Schizophrenia, secondary to delusions and hallucinations cause self-injurious behavior most cases of genital self-mutilation reported in the literature have been in psychotic patients with either functional or organic brain disease [5,14]. Our case is an unusual type of genital self-mutilation in patient suffering from depression without any psychotic features [8,10]. Here in, we report a case of 28 year old male patients suffering from major depressive disorder without psychotic features from the last six month, who presented to us with self-mutilation of genitalia (penis, with both testes and scrotum).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Schizophrenia, secondary to delusions and hallucinations cause self-injurious behavior most cases of genital self-mutilation reported in the literature have been in psychotic patients with either functional or organic brain disease [5,14]. Our case is an unusual type of genital self-mutilation in patient suffering from depression without any psychotic features [8,10]. Here in, we report a case of 28 year old male patients suffering from major depressive disorder without psychotic features from the last six month, who presented to us with self-mutilation of genitalia (penis, with both testes and scrotum).…”
Section: Discussionmentioning
confidence: 97%
“…Psychotic illness includes command hallucinations in schizophrenias patients, bipolar affective disorder with psychotic features and borderline personality disorder [5]. Gender dysphoria, male identification, guilt for sexual offences, sexual conflicts and offences, erotic purposes and body image preoccupation are the other psychopathologies proposed for genital self-mutilation in nonpsychotic illnesses [8].Various syndromes like Lesch-Nyhan syndrome, Cornelia de Lange syndrome and syndromes associated with mental retardation are the other important causes of selfmutilation [9].The rare causes of genitalia self-mutilation are cannabis and cocaine abuse, alcohol intoxication, and amphetamine use [8,10]. Combined mutilation of both penis and scrotum has been reported in patients with command hallucinations and religious delusions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Self-mutilation behavior is being increasingly observed (Ahsaini et al, 2011) and is quite challenging to treat due to the numerous etiologies and complications. The management of urological injuries, a detailed psychiatric evaluation and treatment of hypogonadism should be carried out to ensure the best prognosis for this kind of patient.…”
Section: Discussionmentioning
confidence: 99%
“…Erdur et al reported a 27-year-old patient with schizophrenia who amputated his tongue and penis 1. Ahsaini et al published a report of a 40-year-old man who presented in hemodynamic shock after eviscerating both testes with his fingernails 8. Michopoulos et al reported a 66-year-old man who had been mutilating his fingers for the last six years 5.…”
Section: Discussionmentioning
confidence: 99%